Emergencies (Praxis Educativa, 2025)
Through Resolution No. 2598/23 (November 2023), the Argentine Ministry of Education created the Argentine System of University Academic Credits (SACAU). This system establishes the Student Reference Credit (CRE) as the guiding principle for the design and redesign of curricula. It also supports the translation of curricula into SACAU through training programs and technical assistance and establishes deadlines for university institutions to adapt their current curricula as quickly as possible. The system proposes "implementing new academic policies that guarantee real graduation opportunities and promote a reflection on the university curriculum that takes into account the needs of the context, students, and the learning process" (RM 2598/23).The URGENCY is defined in the document: "The CRE requirement for new applications for official recognition and national validity of university degrees will be effective starting January 1, 2027." The SACAU prescribes a profound curricular reform that entails political decisions in favor of the institutional offerings of each university and that encompasses the meaning of higher education, the non-delegable responsibility of the State as guarantor of rights, and the training of responsible individuals with an ethical and caring conscience, who are reflective and critical, capable of understanding and improving ways of life, in favor of a national culture by promoting the generation and development of knowledge in all its forms. We propose to consider these changes and argue that other urgent issues are problematic for us, those we add to the territories and teaching training specific to this Patagonia we inhabit:- There is an urgent need to challenge these ways of defining public policy—as decisions of what to do or not to do regarding diagnoses, conceptions of meaning, hegemonies, consolidated roles of control, and definitions of time and workloads that are close to a technical rationality that distances itself from the university's commitment to the current historical and social context.- There is an urgent need to sustain education as a political space in the dialectic between the theoretical context and the concrete context, between the reading of the world and the reading of the word, meanings that take shape to the extent of our transformative action with the world.